Efficiency of the transport system operation in separation at the open pit "Dimnjače" - Razić Rusmir; Mašić Sunčica; Brčaninović Muhidin; Alić Nedžad (Mining and Metallurgy Engineering Bor, 2021)
This paper sets out the methodology and presents the results of calculation the efficiency of transport system in separation of the OP "Dimnjače", based on the data of monitoring the operating time and downtime/failure. Properly determined state of operation of the transport system, allows preventive measures and selection of maintenance strategy. Data collection lasted a year, and the data were analyzed, and thus the results are given by month for the transport system as a whole.